Analysis of the Results from In Situ Testing of a Sensor In-Stalled on a Powered Roof Support, Developed by KOMAG, Measuring the Tip to Face Distance - Sławomir Bartoszek; Joanna Rogala-Rojek; Dariusz Jasiulek; Jerzy Jagoda; Krzysztof Turczyński; Marek Szyguła (Energies, 2021)
Mining in underground plants is associated with high risk. Improving work safety and increasing the productivity of longwall systems in the mining industry is a problem considering many criteria. Safety aspects concern both the crew and the machinery. The KOMAG Institute of Mining Technology designed and manufactured a geometry monitoring system based on inclinometers that meet the requirements of the ATEX directive. Monitoring of the roof support geometry is used for the prevention of loss of roof stability: roof fall or/and cave-in. The system was tested on a real object in real conditions.